Variable Thermal Conductivity and Viscosity Flow past a Stretching Porous Surface with Viscous Dissipation through a Porous Medium - Ogunsola, A.W. (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
In this work, we study variable thermal conductivity and viscosity flow past a porous surface with viscous dissipation through a porous medium. We transformed the governing partial differential equations into ordinary differential equations in terms of a suitable similarity variable. We employed Galerkin weighted residual method to solve the resulting non-linear equations. The results show the effects of variable viscosity parameter, variable thermal conductivity parameters and those of viscous dissipation parameter on the flow system.